3D modified graphene-carbon fiber hybridized skeleton/PDMS composites with high thermal conductivity. (7th July 2022) - Li, Chuanyi; Wang, Xianpeng; Li, Yanhua; Wang, Han; Tang, Qunli; Hu, Aiping; Chen, Xiaohua
Abstract: High-efficient heat dissipation has already become a key issue challenging the further development of smart and flexible electronic devices. In this work, a three-dimensional (3D) modified graphene-carbon fiber (MGCF) hybridized skeleton/polydimethylsiloxane (PDMS) composite is prepared. The polyimide (PI) fibers are coated by polyamide acid salt (PAAS)-modified graphene oxide (GO), then freeze-drying technique is used to construct a 3D hybridized structure, followed by high-temperature annealing. Finally, PDMS is impregnated into 3D MGCF hybridized skeletons to generate MGCF/PDMS composites. It is found that GO sheets are covalently welded by PAAS into larger-size GO assemblies, which effectively improves the interfacial interactions and synergistic graphitization between PI molecules and GO sheets. The larger-size graphene assemblies wind and interconnect on the surface of PI-derived carbon fibers to construct a dual-channel 3D thermally conductive network. Such a special structure provides MGCF/PDMS composite with a high thermal conductivity of 1.569 W m −1  K −1 at 2 wt% loading, which is 636% higher than that of pure PDMS. More importantly, MGCF/PDMS composite still displays good mechanical properties with 94.8% of elongation at break and 9.35 MPa of compressive modulus. The outstanding comprehensive properties provide MGCF/PDMS composites with a promising application prospect in lightweight and flexible thermal interface materials (TIMs). Graphical abstract: 3D MGCF hybridized skeletons are effectively prepared by in situ polymerization, freeze-drying and thermal annealing. PAAS-modification significantly increases the lateral size of modified graphene assemblies to construct a complete and continuous 3D two-channel thermally conductive network, which provides MGCF/PDMS composites with excellent heat conduction capabilities as TIMs. Image 1 Highlights: 3D MGCF hybridized skeletons were fabricated by wrapping graphene on carbon fibers. PAAS-modification effectively improves the graphitization degree of 3D skeletons. MGCF/PDMS composites exhibit high thermal conductivity (1.569 W m −1  K −1 ) at 2wt% loading..